ABO blood group antigen therapy: a potential new strategy against solid tumors - Qiong Luo (Nature Portfolio, 2021)
Abstract The economic burden of tumors is increasing, so there is an urgent need to develop new therapies for their treatment. Killing tumors by activating complement is an effective strategy for the treatment. We used the ABO blood group system and the corresponding antibodies to activate the killer cell capacity of the complement system. After the construction of a mouse model containing blood group A antibodies and inoculating colorectal cancer and breast cancer cells into the axillae of the mice, intratumoural injection using a lentivirus carrying a blood group antigen as a drug significantly reduced the tumor volume of the mice. Compared with the control group, the content of the C5b-9 complement membrane attack complex in the tumors of mice treated with the blood group A antigen was significantly increased, and the proportion of NK cells was also significantly increased. In vitro cell-based experiments proved that tumor cells expressing blood group A antigens showed significantly inhibited cell proliferation when added to serum containing blood group A antibodies. These results all prove that the ABO blood group antigen may become a powerful tool for the treatment of tumors in patients.